Regional Competitiveness and Development with the Reference to the Situation in Albania - Mehilli, Terida; Dumi, Alba (Richtmann Publishing, 2011)
Democratic Albanian local governance is a prerequisite to the meaningful decentralization of infrastructure management.When people participate in defining visions for sustainable development for their communities, in formulating strategies for equitable accessto services and resources and in setting priorities for action, they have endorsed. Participation also sharpens their awareness of theinterrelations between economic, social and environment issues. This is a highly significant feature of infrastructure Albanian programsand carries important role for local development. This Albanian reform allows banks to better evaluate the creditworthiness of potentialborrowers, facilitating access to credit for firms and individuals. Albania also strengthened investor protection. A new company lawrequires that disinterested shareholders approve transactions between interested parties and obligates those parties to disclose allinformation on the transaction to the public. The law also reinforces directors’ duties and requires directors, when found liable, to paydamages and return profits to the company. A new bankruptcy law approved during 2008 provides a more efficient framework for closinga business.